Epidemiology and Incidence of Pediatric Concussions in General Aspects of Life - Chang Yaramothu (Brain Sciences, 2019)
Background: Concussions are one of the most common head injuries acquired within the pediatric population. While sport-related concussions are well documented, concussions within other aspects of a child’s life are not as well researched. The purpose of this study is to examine the incidence of a large pediatric concussion population in a broad range of daily activities. Methods: Patients’ gender and nature of injury were extracted from 1408 medical records of patients who were diagnosed with a concussion at Saint Peter’s Sports Medicine Institute. Statistical analyses were conducted for activities and environmental settings using chi-squared tests. Results: Concussions were most prevalent in organized sports (53.3%), followed by injuries within the following settings: school (16.5%), recreational (6.7%), motor vehicle collisions (6.6%), home (5.5%), and other (11.3%). Specifically, soccer (12.9%), school physical education (PE) class (10.6%), and football (9.8%) subcategories recorded the most incidences of concussion. For the PE class cohort (n = 149), significantly more females were diagnosed with a concussion compared to males (p < 0.001). Conclusions: PE-related concussions had the second highest incidence rate after organized sports. A significant gender difference was observed in PE class. Awareness about concussions and methods to reduce the risk of concussion is suggested for PE classes.